2022
DOI: 10.1080/21655979.2022.2056692
|View full text |Cite
|
Sign up to set email alerts
|

Vacuolar protein sorting-associated protein 72 homolog (VPS72) binding to lysine acetyltransferase 5 (KAT5) promotes the proliferation, invasion and migration of hepatocellular carcinoma through regulating phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT) signaling pathway

Abstract: Hepatocellular carcinoma, a fatal malignancy that occurs in the liver, poses a major public health challenge. This paper attempted to clarify the role and mechanism of vacuolar protein sorting-associated protein 72 homolog (VPS72) in the progression of hepatocellular carcinoma. Firstly, VPS72 expression in hepatocellular carcinoma tissues and the prognostic correlation were analyzed by GEPIA2 database. Western blotting and RT-qPCR assays were used to evaluate VPS72 expression in several hepatocellular carcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
(30 reference statements)
0
5
1
Order By: Relevance
“…In this study, CNV-driven VPS72 overexpression activated the malignant behavior of HCC and exerted a strong prognostic effect on HCC patients. A recent study revealed that VPS72 knockdown inhibited the growth and migration of HCC cells in vitro and inhibited the AKT signaling pathway 33 . However, in our study, overexpression of VPS72 promoted the initiation and progression of an oncogene-induced (AKT/β-catenin) mouse HCC model, and targeting VPS72 inhibited the progression of this HCC model, suggesting that VPS72 is more likely to play a role in promoting HCC progression through pathways other than AKT.…”
Section: Discussioncontrasting
confidence: 79%
“…In this study, CNV-driven VPS72 overexpression activated the malignant behavior of HCC and exerted a strong prognostic effect on HCC patients. A recent study revealed that VPS72 knockdown inhibited the growth and migration of HCC cells in vitro and inhibited the AKT signaling pathway 33 . However, in our study, overexpression of VPS72 promoted the initiation and progression of an oncogene-induced (AKT/β-catenin) mouse HCC model, and targeting VPS72 inhibited the progression of this HCC model, suggesting that VPS72 is more likely to play a role in promoting HCC progression through pathways other than AKT.…”
Section: Discussioncontrasting
confidence: 79%
“…Chromatin remodeler CHD7 , a somatic driver candidate in colorectal cancer (CRC), promotes CRC cell growth by binding target gene promoters, encouraging an open chromatin conformation and subsequent transcription, whereas CHD7 knockdown inhibits CRC cell growth [ 74 ]. Similarly, POLR1B knockdown induces lung cancer cell apoptosis [ 75 ], VPS72 knockdown inhibits the proliferation, invasion, and migration of hepatocellular carcinoma (HCC) cells [ 76 ], and UBTF silencing suppresses melanoma cell proliferation [ 77 ]. DPF3 , a chromatin remodeling cofactor significantly downregulated in breast cancer tissue, promoting the proliferation of breast cancer cells, has been suggested as a novel therapeutic target for breast cancer therapy [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Biogrid DataBase (version 4.4; https://thebiogrid.org/ ) is a database that can be used to predict the protein-protein link [ 22 ].…”
Section: Methodsmentioning
confidence: 99%